Wagons Maintenance Performance Analysis at Depot Gerbong Sidotopo, Surabaya - Yosi Pahala; Galih Prananda; Widodo Widodo; Rully Indrawan (Institut Transportasi dan Logistik Trisakti, 2021)
The research objective is to improve the performance of the carriage Depot in terms of maintenance personnel, facilities and equipment to support the operational needs of the wagon facility. The Sidotopo Wagon Depot is one of the Depots that carries out periodic maintenance of wagon facilities in Operation Area 8 Surabaya. In carrying out the maintenance of facilities, there are several obstacles, namely the workload that is not in accordance with regular working hours, the minimum number of employees who have competency certification, several measuring instruments that have not been calibrated and several damaged work facilities and equipment. In this research, which will be a sample of maintenance personnel facilities at the Sidotopo Carriage Depot with a population of 28 people. This research uses the Importance Performance Analysis approach method, Cartesian diagram, validity and reliability test, analysis of characteristics and needs of maintenance personnel and analysis of availability of Depot maintenance facilities and equipment. Research results, found that the number of maintenance personnel needed is 30 maintenance personnel. Also, requires improvement efforts on the performance elements that are included in the main priority, namely; the condition of work equipment, calibration of work equipment and number of maintenance personnel.